The Use of Abdominal Free Fat for Volumetric Augmentation and Primary Dural Closure in Supratentorial Skull Base Surgery: Managing the Stigma of a Temporal Defect - Ackerman, Paul D.; Hammers, Ronald; Ibrahim, Tarik; Origitano, T.C. (Journal of Neurological Surgery Part B: Skull Base, 2012)
The most prominent stigma of supratentorial skull base surgery is the defect caused by wasting of the temporalis muscle by denervation, devascularization, or rotation of the muscle. Any of the above may lead to a unilateral temporal deformity informally referred to patients as “the divot in my head.” Abdominal free fat grafting has been used by surgeons for years to close posterior fossa defects with excellent results. We present our experience using abdominal free fat grafts to improve cosmetic results and to prevent cerebrospinal fluid leaks in supratentorial skull base surgery. The basic technique and its benefits are described.
Keywords: supratentorial skull base surgery; cerebrospinal fluid leak; free fat grafting; dural closure; craniotomy